2013
DOI: 10.4236/psych.2013.410a002
|View full text |Cite
|
Sign up to set email alerts
|

Working Memory and Reading Development

Abstract: Purpose: To evaluate the development of working memory and reading in proficient students from 1st to 4th year of elementary school. Method: Participants were 19 people of both genders, with an average age of 8.26 years, enrolled between the 1st and 4th year of elementary school, who met the proposed inclusion criteria and were proposed and evaluated for working memory and reading level. Results: There're no significant differences in the level of reading and working memory between genders male and female. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…During literacy development, inhibitory control supports an emerging reader by suppressing irrelevant and distracting information both in their environment and in their prepotent responses to the visual stimulus of written language (Altemeier et al, 2008;Dehaene et al, 2015). Working memory allows the reader to retain and manipulate the phonological and visual information necessary to learn the mappings between written language and its corresponding sounds and meanings-decoding ability (Ferreira et al, 2013). Cognitive flexibility, the ability to switch between different cognitive tasks, allows an emerging reader to think about the properties of words beyond their semantic information and develop the meta-linguistic knowledge to understand the segmental nature of language, which in turn allows the reader to map segments to individual symbols (e.g.…”
Section: Executive Functions and Literacymentioning
confidence: 99%
“…During literacy development, inhibitory control supports an emerging reader by suppressing irrelevant and distracting information both in their environment and in their prepotent responses to the visual stimulus of written language (Altemeier et al, 2008;Dehaene et al, 2015). Working memory allows the reader to retain and manipulate the phonological and visual information necessary to learn the mappings between written language and its corresponding sounds and meanings-decoding ability (Ferreira et al, 2013). Cognitive flexibility, the ability to switch between different cognitive tasks, allows an emerging reader to think about the properties of words beyond their semantic information and develop the meta-linguistic knowledge to understand the segmental nature of language, which in turn allows the reader to map segments to individual symbols (e.g.…”
Section: Executive Functions and Literacymentioning
confidence: 99%
“…Studies suggested that the LA is accompanied by reading, especially in comprehension, decoding skills, and fluency [19] . Working memory (WM) refers to the ability to retain and manipulate information temporally during performance of cognitive tasks such as comprehension, reasoning, and learning [20] .…”
Section: Phonological Processingmentioning
confidence: 99%
“…The WM is responsible for the temporary storage of information while performing cognitive tasks such as reasoning, comprehension and learning (Alloway, Gathercole, & Elliott, 2010;Carrilo-Mora, 2010;Voorde, Roeyers, & Wiersema, 2010, Ferreira, Valentin, & Ciasca, 2013. According to the model of Baddeley and Hitch (1974) and Barkley (2002), the WM is responsible for maintaining the information recently processed and the establishment of connections with the new information.…”
Section: Introductionmentioning
confidence: 99%